MEDIA SOSIAL: PERILAKU SOSIAL ASMARA DALAM PERUBAHAN SOSIAL REMAJA - Sesady, Siti Fatmawati; RAF, Nuvida; Muhammad, Rahmat (Universitas Tanjungpura, 2022)
Teenagers are users who use social media as a forum for communication, seeking information, and being hyperactive in publishing daily life with a better lifestyle, even though it is completely untrustworthy or even used as a reference in socializing. Knowing the phenomenon of publication of social behavior in romantic relationships and very close relationships with each other, knowing as seen in the Citayam Teen phenomenon in romantic relationship behavior which is known to be viral on social media can affect teenagers social change, as the purpose of this study. This study uses qualitative research methods with the aim of looking at existing phenomena and then uses a descriptive approach to describe the impact of adolescent social behavior in social media that will affect social change for their adolescent peers. Based on the results of the study, the influence given can be in the form of positive and negative influences. Positive influence, can give youth space to innovate, be creative, and play a global role and get emotional support from others, as well as provide income. Meanwhile, by going viral on social media, the social behavior they display can have a negative effect, by expecting justification, and acknowledgment of the behavior of romantic relationships and friendships shown on social media without understanding that it has violated cultural norms by adopting people's cultures. outsiders who are considered to follow the development of modern times, then allow their peers and peers to make it as something that can be imitated by expecting popularity even though it has violated cultural norms. Likewise, these actions can also have a negative impact through negative comments on social media regarding their social behavior that is not in accordance with the surrounding norms and culture.